Puncture-resistant tread rubber composition for bicycles and electric vehicles as well as mixing method and performance of puncture-resistant tread rubber composition
By introducing surface-treated aramid staple fibers into the bicycle tread rubber composition and optimizing the rubber substrate and additive system, the problem of difficult puncture resistance and elasticity in the prior art is solved, and a higher level of puncture resistance and better elastic recovery.
Patent Information
- Application Number
- CN202411600649.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-07
AI Technical Summary
The existing bicycle tread rubber compositions are difficult to achieve a good balance between puncture resistance and elasticity, and cracks or fractures are prone to occur in low temperature environments.
A carefully selected rubber substrate and additive system is used, combined with surface-treated aramid staple fibers, to form an improved thorn-resistant rubber composition for bicycle and electric vehicles. The composition improves the compatibility and interface bonding force of the fibers with the rubber matrix by introducing aramid staple fibers into the rubber matrix and surface treatment with a silane coupling agent.
It significantly improves the puncture resistance of the material, while maintaining good elasticity and aging resistance, achieving a good balance between puncture resistance and elasticity.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire manufacturing, and in particular to a puncture-resistant tread rubber composition for bicycles and electric vehicles, a mixing method and performance. Background Art
[0002] Bicycle tires need to have good puncture resistance and elasticity in daily use to cope with sharp objects such as nails and gravel in complex road conditions, while maintaining good riding comfort. However, the existing bicycle tread rubber composition has certain deficiencies in the balance between these two aspects. Traditional rubber tread materials are often based on natural rubber and styrene-butadiene rubber. Although these two rubbers have good elasticity, their puncture resistance is relatively weak, especially when facing sharp objects, they are easily damaged, which affects the service life of the tire.
[0003] In order to improve the puncture resistance of tires, the puncture resistance of rubber materials is usually enhanced by adding hard fillers such as white carbon black and calcium carbonate. However, excessive use of these rigid materials often leads to a decrease in the elasticity of the rubber and reduced comfort of the tire during riding. At the same time, too much filler may also increase the brittleness of the rubber, making it prone to cracking or breaking under more severe temperature conditions (such as low temperature environments).
[0004] As a high-strength, high-modulus material, aramid fiber has been widely used in bulletproof and puncture-proof materials. Introducing aramid short fibers into rubber tread materials can significantly improve the material's puncture resistance. However, due to the poor compatibility between aramid fibers and the rubber matrix, the fibers tend to agglomerate in the rubber matrix, affecting the uniformity and overall performance of the material.
[0005] In addition, in order to ensure the weather resistance and aging resistance of rubber materials, existing tread rubber formulas usually add additives such as antioxidants and protective wax to improve the aging resistance and oxidation resistance of materials in long-term use. However, how to further improve the puncture resistance and elasticity of tires while ensuring the aging resistance, oxidation resistance and weather resistance of tires is still an important challenge facing existing technologies. Summary of the invention
[0006] In order to overcome these technical difficulties, the present invention provides an improved puncture-resistant tread rubber composition for bicycles and electric vehicles. The composition significantly improves the puncture resistance of the material and maintains good elasticity and aging resistance through a carefully selected rubber base material and an additive system, combined with surface-treated aramid short fibers, thereby achieving a good balance between puncture resistance and elasticity.
[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions: A puncture-resistant tread rubber composition for bicycles and electric vehicles, wherein the tread rubber composition is prepared by mixing raw materials including the following components based on 100 parts by weight of the rubber component: Natural rubber: 40-60 parts; Styrene butadiene rubber: 40-60 parts; Zinc oxide: 3.0-8.0 parts; Stearic acid: 1.5-3.0 parts; White carbon black: 30-40 parts; Active calcium carbonate: 20-30 parts; Aramid staple fiber: 0.3-10 parts; Activator PEG-4000: 1.0-3.0 parts; Silane coupling agent: 2.5-5.0 parts; Modulus enhancer: 1.5-3.5 parts; Anti-aging agent: 0.5-1.5 parts; Protective wax: 1.0-2.0 parts; Sulfur: 1.5-3.0 parts; Accelerator NS: 1.0-2.0 parts; Accelerator TMTD: 0.20-0.0.35 parts; Accelerator M: 0.15-0.30 parts.
[0008] Preferably, the tread rubber composition is prepared by mixing raw materials including the following components based on 100 parts by weight of the rubber component: Natural rubber: 45-55 parts; Styrene butadiene rubber: 45-55 parts; Zinc oxide: 4.0-6.0 parts; Stearic acid: 1.5-2.5 parts; White carbon black: 32-35 parts; Active calcium carbonate: 22-28 parts; Aramid staple fiber: 0.4-0.6 parts; Activator PEG-4000: 1.5-2.5 parts; Silane coupling agent: 3.0-4.0 parts; Modulus enhancer: 1.5-3.5 parts; Anti-aging agent: 0.5-1.5 parts; Protective wax: 1.0-2.0 parts; Sulfur: 2.0-3.0 parts; Accelerator NS: 1.0-2.0 parts; Accelerator TMTD: 0.20-0.0.30 parts; Accelerator M: 0.15-0.25 parts.
[0009] Preferably, the mixing raw materials of the tread rubber composition further include 1.5-3.0 parts of color rubber R1005, 0.2-0.5 parts of color rubber R104A, and 1.0-2.0 parts of titanium dioxide.
[0010] Preferably, the styrene-butadiene rubber is styrene-butadiene rubber 1502, the modulus enhancer is modulus enhancer HMZ, the protective wax is protective wax BS, and the silane coupling agent is silane coupling agent 69.
[0011] Preferably, the aramid staple fibers have a fiber length of 0.2-1.5 mm.
[0012] Preferably, the aramid staple fibers are surface treated with a silane coupling agent.
[0013] Preferably, the tread rubber composition further contains thermoplastic elastomer TPE in an amount of 3.0-6.0 parts.
[0014] Furthermore, the present invention also discloses a mixing method of the tread rubber composition, which comprises the following steps: 1) Mix natural rubber, styrene-butadiene rubber and 60-80% by mass of white carbon black in a GK255 internal mixer, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 2) Add a first-stage mixed rubber, silane coupling agent, remaining white carbon black and fine materials except sulfur and accelerator into the internal mixer, pressurize for 30 seconds, then add activated calcium carbonate, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 3) Add the second-stage mixed rubber, sulfur and accelerator into the internal mixer, and the sulfur adding temperature should be ≤100℃; pressurize for 20 seconds and lift the top bolt, pressurize for 30 seconds and lift the top bolt, pressurize for 20 seconds, discharge the rubber to the first tablet press through the roller, discharge the rubber to the second tablet press, tamp the rubber left and right twice to produce sheets.
[0015] Furthermore, the present invention also discloses a puncture-resistant bicycle tire, wherein the tread of the tire is prepared by vulcanizing the tread rubber composition.
[0016] The present invention adopts the above technical solution, through the carefully selected rubber substrate and additive system, and combined with the surface-treated aramid staple fibers, which not only significantly improves the puncture resistance of the material, but also maintains good elasticity and aging resistance, thereby achieving a good balance between puncture resistance and elasticity. The details are as follows: 1. Improved puncture resistance The present invention significantly enhances the puncture resistance of the rubber material by introducing aramid short fibers into the tread rubber composition. Aramid fibers have extremely high strength and toughness, and can effectively block external puncture forces, such as the invasion of gravel, nails, etc., thereby greatly improving the durability and protective performance of the tire. Compared with traditional rubber compositions, the rubber material of the present invention can provide stronger anti-puncture protection in complex road conditions, extending the service life of the tire.
[0017] 2. Maintain good elasticity and comfort Despite the addition of rigid reinforcement materials such as aramid short fibers and white carbon black, the present invention ensures the elasticity and recovery of the material through formula optimization, such as adding thermoplastic elastomer (TPE). The introduction of TPE enables the tread rubber to have high puncture resistance while still maintaining good elastic recovery, ensuring riding comfort and the shock resistance of the tire, and solving the problem of difficult balance between hardness and elasticity in traditional high puncture resistance rubber formulas.
[0018] 3. Improved the interfacial bonding between the fiber and the rubber matrix The present invention uses a silane coupling agent to perform surface treatment on aramid staple fibers, thereby effectively improving the compatibility of the fibers with the rubber matrix and enhancing the interfacial bonding force. Untreated aramid fibers tend to form agglomerates in the rubber matrix, resulting in uneven performance. The surface treatment technology in the present invention solves this problem, allowing the fibers to be evenly dispersed in the rubber matrix, further improving the mechanical properties and comprehensive properties of the material, and ensuring a balance between puncture resistance and elasticity.
[0019] 4. Improved the aging resistance, weather resistance and oxidation resistance of materials The patent introduces a combination of antioxidants, protective wax and other additives, which effectively improves the aging resistance of rubber materials and delays the aging problem of rubber due to oxidation, ultraviolet rays and ozone erosion during long-term use. In addition, the protective wax and other additives in the formula can effectively reduce the oxidation rate of the rubber surface, so that the rubber maintains good performance during long-term use and is suitable for different climates and usage environments.
[0020] 5. Improved the processing properties of the formula This patent precisely controls process parameters such as Mooney viscosity during the mixing process, ensuring that the raw materials can be fully dispersed during the mixing process to avoid uneven processing. At the same time, by controlling the temperature and time during the vulcanization process, the tread rubber composition of the present invention can achieve better processing stability, ensuring that the rubber material has good processability and controllability during the production process.
[0021] 6. Balance the hardness and flexibility of the material By combining appropriate amounts of white carbon black and active calcium carbonate fillers, as well as the use of modulus enhancers, the formulation of the present invention optimizes the flexibility of the material while maintaining a certain hardness. The composition not only has excellent puncture resistance, but also ensures the flexibility of the tire within a certain range, making it puncture-resistant and fatigue-resistant, and suitable for long-term, high-intensity use scenarios. DETAILED DESCRIPTION
[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1: 1. Recipe: Natural rubber: 50 parts Styrene butadiene rubber 1502: 50 parts Zinc oxide: 5.0 parts Stearic acid: 2.0 parts White carbon black: 35 parts Active calcium carbonate: 25 parts Aramid staple fiber: 0.5 parts (surface treated with silane coupling agent) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Modulus enhancer HMZ: 2.5 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.5 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.2 parts.
[0024] 2. Surface treatment method of aramid staple fiber silane coupling agent 1) Cleaning: Clean the aramid staple fibers with deionized water or ethanol solution to remove dust, oil and impurities that may exist on the fiber surface. This ensures that the fiber surface is clean, which is conducive to the subsequent attachment of the silane coupling agent.
[0025] 2) Drying: Place the cleaned aramid fiber in an oven, usually at 80-100°C for 2-4 hours, until there is no residual moisture on the fiber surface.
[0026] 3) Prepare silane coupling agent solution. The commonly used silane coupling agent is γ-aminopropyltriethoxysilane (KH-550). Dissolve the silane coupling agent in a certain proportion (usually 0.5-2%) in an aqueous ethanol solution (95% ethanol and 5% water), stir thoroughly to ensure that the solution is uniform.
[0027] 4) Completely immerse the dried aramid staple fibers in the prepared silane coupling agent solution. During the immersion process, stirring or shaking is required to allow the fiber surface to fully contact the silane coupling agent. The immersion time is usually 30 minutes to 1 hour to ensure that the fiber surface reacts completely with the silane coupling agent.
[0028] 5) Take the aramid fiber impregnated with silane coupling agent out of the solution, place it at room temperature to dry, and transfer it to an oven after the surface moisture evaporates. Heat treatment is performed at 110-120°C for 2-4 hours to promote the reaction of the silane coupling agent with the hydroxyl groups on the fiber surface to form siloxane bonds. This process can not only enhance the compatibility of the fiber with the rubber matrix, but also form a stable coupling layer on the fiber surface, improving the heat resistance and anti-aging properties of the fiber.
[0029] 6) After drying and heat treatment, the aramid fiber is cooled to room temperature. A thin film of silane coupling agent has formed on the fiber surface, and the subsequent rubber mixing process can be carried out. Simple mechanical treatment (such as cutting or uniform dispersion) can be selected to ensure the uniform distribution of the fiber in the rubber matrix.
[0030] 3. Mixing method The mixing method of the tread rubber composition comprises the following steps: 1) Mix natural rubber, styrene-butadiene rubber and 60-80% by mass of white carbon black in a GK255 internal mixer, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 2) Add a first-stage mixed rubber, silane coupling agent, remaining white carbon black and fine materials except sulfur and accelerator into the internal mixer, pressurize for 30 seconds, then add activated calcium carbonate, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 3) Add the second-stage mixed rubber, sulfur and accelerator into the internal mixer, and the sulfur adding temperature should be ≤100℃; pressurize for 20 seconds and lift the top bolt, pressurize for 30 seconds and lift the top bolt, pressurize for 20 seconds, discharge the rubber to the first tablet press through the roller, discharge the rubber to the second tablet press, tamp the rubber left and right twice to produce sheets.
[0031] Embodiment 2: 1. Recipe Natural rubber: 45 parts Styrene butadiene rubber 1502: 55 parts Zinc oxide: 4.5 parts Stearic acid: 2.0 parts White carbon black: 34 parts Active calcium carbonate: 28 parts Aramid staple fiber: 0.6 parts (surface treated with silane coupling agent) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Modulus enhancer HMZ: 3.0 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.0 parts Accelerator NS: 1.2 parts Accelerator TMTD: 0.30 parts Accelerator M: 0.18 parts.
[0032] 2. Mixing method The surface treatment and mixing method of the silane coupling agent are similar to those of Example 1.
[0033] Embodiment 3: Natural rubber: 55 parts Styrene butadiene rubber 1502: 45 parts Zinc oxide: 6.0 parts Stearic acid: 2.5 parts White carbon black: 33 parts Active calcium carbonate: 26 parts Aramid staple fiber: 0.4 parts (surface treated with silane coupling agent) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 4.0 parts Modulus enhancer HMZ: 2.0 parts Anti-aging agent RD: 1.5 parts Protective wax BS: 2.0 parts Sulfur: 2.0 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.20 parts.
[0034] 2. Mixing method The mixing method is the same as that in Example 1.
[0035] Comparative Example 1 (untreated aramid staple fiber): Natural rubber: 50 parts Styrene butadiene rubber 1502: 50 parts Zinc oxide: 5.0 parts Stearic acid: 2.0 parts White carbon black: 35 parts Active calcium carbonate: 25 parts Aramid staple fiber: 0.5 parts (without silane coupling agent surface treatment) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Modulus enhancer HMZ: 2.5 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.5 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.2 parts.
[0036] 2. Mixing method The mixing method is the same as that in Example 1.
[0037] Comparative Example 2 (without aramid staple fiber): Natural rubber: 55 parts Styrene butadiene rubber 1502: 45 parts Zinc oxide: 5.0 parts Stearic acid: 2.0 parts White carbon black: 35 parts Active calcium carbonate: 25 parts Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Modulus enhancer HMZ: 2.5 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.5 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.2 parts.
[0038] 2. Mixing method The mixing method is the same as that in Example 1.
[0039] Comparative Example 3 (no modulus enhancer added): Natural rubber: 50 parts Styrene butadiene rubber 1502: 50 parts Zinc oxide: 5.0 parts Stearic acid: 2.0 parts White carbon black: 35 parts Active calcium carbonate: 25 parts Aramid staple fiber: 0.5 parts (surface treated with silane coupling agent) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.5 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.2 parts.
[0040] 2. Mixing method The surface treatment and mixing method of the silane coupling agent are similar to those of Example 1.
[0041] Comparative Example 4 (no activated calcium carbonate added) 1. Recipe: Natural rubber: 50 parts Styrene butadiene rubber 1502: 50 parts Zinc oxide: 5.0 parts Stearic acid: 2.0 parts White carbon black: 35 parts Aramid staple fiber: 0.5 parts (surface treated with silane coupling agent) Activator PEG-4000: 2.0 parts Silane coupling agent 69: 3.5 parts Modulus enhancer HMZ: 2.5 parts Anti-aging agent RD: 1.0 part Protective wax BS: 1.5 parts Sulfur: 2.5 parts Accelerator NS: 1.5 parts Accelerator TMTD: 0.25 parts Accelerator M: 0.2 parts.
[0042] 2. Mixing method The surface treatment and mixing method of the silane coupling agent are similar to those of Example 1.
[0043] The following experimental data, by comparing the examples and comparative examples, focus on demonstrating the advantages of the present invention, especially in terms of puncture resistance and elastic balance.
[0044] Experimental indicators description: 1. Puncture strength (N): reflects the strength of the material when it is punctured. The test method is to pierce the surface of the material with a standard hardness probe to measure its maximum tolerance.
[0045] 2. Elastic recovery rate (%): The ability of a material to return to its original shape after being compressed. The higher the value, the better the elasticity of the material.
[0046] 3. Elasticity retention rate after aging (%): The ability of the material to maintain elastic recovery after aging (such as high temperature, ultraviolet rays).
[0047] 4. Mooney viscosity (ML1+4): Mooney viscosity reflects the processing performance and viscosity of rubber materials. A low value indicates that it is easy to process.
[0048] Experimental data of embodiment and comparative example: Group Puncture strength(N) Elastic recovery rate (%) Elasticity retention after aging (%) Mooney viscosity (ML1+4, 100°C) Example 1 624 70 85 50 Example 2 642 72 87 52 Example 3 630 73 88 54 Comparative Example 1 (untreated fiber) 594 65 80 55 Comparative Example 2 (no fiber) 526 80 85 53 Comparative Example 3 (without enhancer) 600 65 78 55 Comparative Example 4 (Inactive Calcium Carbonate) 612 68 82 54 Data Analysis: 1. Puncture strength Example 2 showed the highest puncture strength (642 N), followed by Example 3 (630 N) and Example 1 (624 N). This indicates that the puncture strength is maximized under the combination of aramid staple fiber treatment and reinforcing agent, activated calcium carbonate.
[0049] In comparison, the puncture strengths of Comparative Example 1 (untreated fiber) and Comparative Example 3 (no reinforcing agent) are lower, being 594 N and 600 N, respectively, indicating that fiber treatment and the introduction of reinforcing agent are critical to improving the puncture strength.
[0050] Comparative Example 2 (no fiber) has the lowest puncture strength of only 526 N, indicating that fiber is an important factor in enhancing puncture resistance.
[0051] 2. Elastic recovery rate Although Comparative Example 2 (no fiber) performed poorly in terms of puncture strength, it had the highest elastic recovery rate of 80%, indicating that removing the fiber reduced the puncture strength but improved the elastic recovery performance.
[0052] The elastic recovery rate in the examples was maintained between 70% and 73%, although slightly lower than that in Comparative Example 2, but these examples maintained a good balance between puncture strength and elasticity.
[0053] Comparative Examples 1 and 3 had lower elastic recovery (65%), showing that the combination of untreated fibers and no reinforcement had a negative impact on elasticity.
[0054] 3. Elasticity retention after aging Example 3 showed the best elasticity retention after aging (88%), followed by Example 2 (87%) and Example 1 (85%), indicating that the use of aramid staple fibers treated with a silane coupling agent and a reinforcing agent significantly improved the aging properties of the material.
[0055] Comparative Example 1 (80%), Comparative Example 3 (78%) and Comparative Example 4 (82%) all showed poor elastic retention after aging, indicating that the combination of untreated fibers, no reinforcing agent or no active calcium carbonate led to a decrease in the aging performance of the material.
[0056] 4. Mooney viscosity The Mooney viscosity of Example 1 is the lowest (50 ML), indicating that the material has the best processing performance. The Mooney viscosities of Examples 2 and 3 are 52 and 54 ML, respectively, which are slightly higher but still within an acceptable range.
[0057] The Mooney viscosity of the comparative examples is generally high, especially that of comparative examples 1 and 3, which reaches 55 ML, indicating that the removal of fiber treatment or the absence of reinforcing agent leads to poor processability.
[0058] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.
Claims
1. A puncture-resistant tread rubber composition for bicycles and electric vehicles, characterized in that: The tread rubber composition is prepared by mixing raw materials including the following components based on 100 parts by weight of the rubber component: Natural rubber: 40-60 parts; Styrene butadiene rubber: 40-60 parts; Zinc oxide: 3.0-8.0 parts; Stearic acid: 1.5-3.0 parts; White carbon black: 30-40 parts; Active calcium carbonate: 20-30 parts; Aramid staple fiber: 0.3-10 parts; Activator PEG-4000: 1.0-3.0 parts; Silane coupling agent: 2.5-5.0 parts; Modulus enhancer: 1.5-3.5 parts; Anti-aging agent: 0.5-1.5 parts; Protective wax: 1.0-2.0 parts; Sulfur: 1.5-3.0 parts; Accelerator NS: 1.0-2.0 parts; Accelerator TMTD: 0.20-0.0.35 parts; Accelerator M: 0.15-0.30 parts.
2. The tread rubber composition according to claim 1, characterized in that: The tread rubber composition is prepared by mixing raw materials including the following components based on 100 parts by weight of the rubber component: Natural rubber: 45-55 parts; Styrene butadiene rubber: 45-55 parts; Zinc oxide: 4.0-6.0 parts; Stearic acid: 1.5-2.5 parts; White carbon black: 32-35 parts; Active calcium carbonate: 22-28 parts; Aramid staple fiber: 0.4-0.6 parts; Activator PEG-4000: 1.5-2.5 parts; Silane coupling agent: 3.0-4.0 parts; Modulus enhancer: 1.5-3.5 parts; Anti-aging agent: 0.5-1.5 parts; Protective wax: 1.0-2.0 parts; Sulfur: 2.0-3.0 parts; Accelerator NS: 1.0-2.0 parts; Accelerator TMTD: 0.20-0.0.30 parts; Accelerator M: 0.15-0.25 parts.
3. The tread rubber composition according to claim 1, characterized in that: The mixed raw materials of the tread rubber composition also include 1.5-3.0 parts of color rubber R1005, 0.2-0.5 parts of color rubber R104A, and 1.0-2.0 parts of titanium dioxide.
4. The tread rubber composition according to claim 1, characterized in that: The styrene-butadiene rubber is styrene-butadiene rubber 1502, the modulus enhancer is modulus enhancer HMZ, the protective wax is protective wax BS, and the silane coupling agent is silane coupling agent 69.
5. The tread rubber composition according to claim 1, characterized in that: Aramid staple fibers have a fiber length of 0.2-1.5 mm.
6. The tread rubber composition according to claim 1 or 5, characterized in that: The aramid staple fibers are surface treated with a silane coupling agent.
7. The tread rubber composition according to claim 1, characterized in that: The tread rubber composition also contains thermoplastic elastomer TPE in an amount of 3.0-6.0 parts.
8. The mixing method of the tread rubber composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: 1) Mix natural rubber, styrene-butadiene rubber and 60-80% by mass of white carbon black in a GK255 internal mixer, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 2) Add a first-stage mixed rubber, silane coupling agent, remaining white carbon black and fine materials except sulfur and accelerator into the internal mixer, pressurize for 30 seconds, then add activated calcium carbonate, pressurize to 120℃, lift the top bolt, and pressurize to 150℃ to discharge the rubber; 3) Add the second-stage mixed rubber, sulfur and accelerator into the internal mixer, and the sulfur adding temperature should be ≤100℃; pressurize for 20 seconds and lift the top bolt, pressurize for 30 seconds and lift the top bolt, pressurize for 20 seconds, discharge the rubber to the first tablet press through the roller, discharge the rubber to the second tablet press, tamp the rubber left and right twice to produce sheets.
9. A puncture-resistant bicycle tire, characterized in that: The tread of the tire is prepared by vulcanizing the tread rubber composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Solid tire base rubber material
CN103044724A
Mine tire and preparation method thereof
CN105037853A
High-performance rubber composition for off-road passenger car tire sidewalls
CN105885123A
Tire tread rubber for preventing bottom crack of pattern groove and preparation method of tire tread rubber
CN113861520A
The snow tire rubber composition using surface-treatedshort fiber
KR1020080020207A
Cited By
Polymer memory rubber for puncture-resistant and leakage-proof tires
CN121930558A